Analysis of the Impact of Engineering Construction on the near Built Seawalls Based on PLAXIS. Issue 1 (April 2020) - Tang, Mingli; Yao, Yongxin; Shi, Yannan; Yu, Jiongqi
Abstract: The article analyzes the impact of a constructing sewage treatment plant on the built seawall nearly by PLAXIS finite element software, located on the coast eastern Zhejiang. As the construction carrying on, the settlement and horizontal displacement are gradually increasing on the top and backwater slope of the seawall. The settlement on the top of Seawalls is 35.91 cm, the horizontal displacement is 50.76 cm; the settlement on the back slope is 71.45 cm, the horizontal displacement is 48.54cm. During the construction process, settlement increase rate at the foot of the backwater slope was significantly larger than that at the top of the seawalls. The horizontal displacement increase rate at the top of the seawalls was slightly larger than that at the foot of the backwater slope. The settlement and horizontal displacement of the seawall exceed the normal allowable deformation, which threatens the safety of the seawall. It is necessary to take reinforcement measures for the seawall to ensure safe operation.